Combine treatment with N-acetylcysteine, anti-CD4/CD8 antibodies and physical exercise reduces histopathological damage in salivary glands of spontaneously diabetic mice - Netto, Raphael Oliveira Ramos Franco; Moura, Eliézer Guimarães; Ferretti, Renato [UNESP]; de Andrade Araújo, Magda Jaciara; Mâncio, Rafael Dias; da Silva, Rodrigo Eduardo; Cajazeiro, Débora Chaves; Fernandes, Victor Augusto Ramos; Bortolato, Renato Sartori; Col, Luan Oenning; Caldeira, Eduardo José (My University, 2021)
Background and aims: The reactive oxygen species (ROS) shows intensification of tissue damage caused by type I diabetes mellitus, and N-acetylcysteine (NAC) can modulate this process by reducing its action. However, in diabetics, NAC seems to potentiate these damages because it stimulates a high infiltration of CD4 and CD8 T lymphocytes, which leads to an important therapeutic association with anti-CD4 / CD8 antibodies. Besides, physical exercise can complement this treatment by stimulating the body’s natural antioxidant defense. The purpose of this study was to analyze the effects of a combined treatment with NAC, anti-CD4 / CD8, and physical exercise on the reduction of damage in the salivary tissues on NOD mice. Material and methods: Female mice were divided into 5 groups with 6 animals each, composed by: Balb/c; NOD; NOD + Ex; NOD + NAC + CDs NOD + NAC + CDs + Ex. The NAC was applied intraperitoneally for 21 days at a dosage of 50mg/kg. The anti-CD4/CD8 were applied intravenously at a dosage of 25 µg/ml on days 0, 7, 14, and 21. During the experimental period, the animals of the exercise groups were subjected daily to 30 minutes of swimming exercise. After 21 days, the tissues were assessed by light microscopy analysis, stereological and immunofluorescence techniques for verification of INS-R insulin receptors. Results: For animals in the NOD + Ex groups; NOD + NAC + CDs; NOD + NAC + CDs + Ex, it was noticed a decrease in lymphocytes and inflammatory processes, as well as a significant increase in the relative neutrophils numbers. There was also a statistically significant difference in the increase of nuclear, and cytoplasmic volume, and an intense INR-S marking when compared to the NOD group without treatment. Conclusion: The therapy used, when associated with NAC to anti-CD4/CD8 promoted the recovery of glandular architecture and INS-R, along with benefit in the reduction of inflammatory processes. It was also found that physical exercise potentiated the therapeutic action of the drug in the tissue restructuring of the salivary glands.
Keywords: Diabetes mellitus type I; N-acetylcysteine; Oxidative stress; Physical exercise